Transformational Leadership on Work Performance in the Pharmaceutical Industry in Malaysia: an Overview - Normen Ahamed Mafaz, Mohamed; Abdullah, Nor’ Ain (Journal of World Science, 2024)
The pharmaceutical sector is characterized by dynamic and highly regulated industry, where effective leadership is critical for achieving business objectives and ensuring the well-being of employees. Furthermore, transformational leadership, a style known for inspiring and motivating followers to achieve their full potential, has gained prominence in the recent discourse on leadership effectiveness. The objective of this paper is to review the relevant literature on transformational leadership and the pharmaceutical industry in Malaysia, highlighting the key components and principles of transformational leadership and their potential applicability in a healthcare setting. A quantitative method is employed to achieve the objective of the study and by using secondary data from Scopus database between the year 1990-2023, the study found that the absence of recorded publications on transformational leadership within the Malaysian pharmaceutical industry underscores a significant research gap. Scholars should prioritize and dedicate efforts to investigate the leadership dynamics within this specific industry, contributing to the dearth of literature in this area. The study contributes to the existing body of knowledge in the field of transformational leadership on work performance in the pharmaceutical industry in Malaysia which will be helpful for the academicians to conduct further examinations on the pharmaceutical industry.